2005
DOI: 10.1038/sj.onc.1208753
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of H-RAS-mediated oncogenic transformation in a genetically defined human ovarian cancer model

Abstract: RAS is a small GTP binding protein mutated in approximately 30% human cancer. Despite its important role in the initiation and progression of human cancer, the underlying mechanism of RAS-induced human epithelial transformation remains elusive. In this study, we probe the cellular and molecular mechanisms of RAS-mediated transformation, by profiling two human ovarian epithelial cell lines. One cell line was immortalized with SV40 T/t antigens and the human catalytic subunit of telomerase (T29), while the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Although originally identified as a potential tumor suppressor gene in NIH3T3 cells (12), the precise roles of TSG101 in tumorigenesis remain undefined. Previously, we identified TSG101 as a downstream target of oncogenic RAS up-regulated during in vitro transformation of human ovarian epithelial cells (27,36). This increased expression of TSG101 is also observed in ovarian cancer patients because more than 70% of ovarian carcinomas express elevated levels of TSG101.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally identified as a potential tumor suppressor gene in NIH3T3 cells (12), the precise roles of TSG101 in tumorigenesis remain undefined. Previously, we identified TSG101 as a downstream target of oncogenic RAS up-regulated during in vitro transformation of human ovarian epithelial cells (27,36). This increased expression of TSG101 is also observed in ovarian cancer patients because more than 70% of ovarian carcinomas express elevated levels of TSG101.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified TSG101 as a downstream target of the RAS oncogene in a genetically defined human ovarian cancer model (27). To investigate the clinical implication of RASmediated TSG101 up-regulation in human ovarian surface epithelial cells, we probed the expression levels of TSG101 in EOC using human ovarian cancer tissue arrays.…”
Section: Resultsmentioning
confidence: 99%
“…2-DE Analysis-2-DE proteomics analysis was performed as described previously (34,35). Briefly cells were trypsinized, washed in PBS, and lysed in buffer containing the following: 7 M urea, 2 M thiourea, 4% CHAPS, 1 mM EDTA, 1 mM EGTA, 60 mM DTT, 1 mM PMSF, 25 g/ml leupeptin, 10 g/ml aprotinin, 1 mM benzamidine, 1 mM sodium orthovanadate, and 1 mM microcystin.…”
Section: Methodsmentioning
confidence: 99%
“…The immortalized but non-oncogenic T29 cells were further transformed by introducing oncogenic HRas V12 to generate the T29H cell line, which resembles natural ovarian cancer in several aspects (10,12). Functional proteomics analysis of Ras-mediated transformation in these cell lines enabled the identification of proteins targeted by Ras that mediate cellular metabolism, apoptosis, and the methylation pathways (10).…”
mentioning
confidence: 99%
“…The immortalized but non-oncogenic T29 cells were further transformed by introducing oncogenic HRas V12 to generate the T29H cell line, which resembles natural ovarian cancer in several aspects (10,12). Functional proteomics analysis of Ras-mediated transformation in these cell lines enabled the identification of proteins targeted by Ras that mediate cellular metabolism, apoptosis, and the methylation pathways (10). Taking advantage of the Ras-T29H ovarian epithelial cell model, Cheng's group also found that the OPCML (opioid-binding protein/cell adhesion molecule-like) gene is epigenetically regulated by Ras in oncogenic transformation (11).…”
mentioning
confidence: 99%